Antioxidant activity Antioxidant activity of ethanol extract of bitti leaves (Vitex cofassus Reinw. ex. Blume) using the dpph free radical scavenging method - Bahari, Dita Wulan; Suhaenah, Asriani; Muflihunna, A. (PHARMACY UMI JOURNAL SYSTEM, 2024)
Antioxidants are compounds that can counteract free radicals in the body, reduce oxidation in cells and cell damage. The purpose of this study was to determine the antioxidant activity of ethanol extract of bitti leaves (Vitex cofassus Reinw. Ex. Blume with DPPH (2,2- diphenyl-1-picrylhydrazyl) scavenging method. The absorbance was measured by UV-Vis spectrophotometer at 510 nm wavelength. The results showed the presence of antioxidant activity with IC50 value of 56.59 μg/mL with strong antioxidant activity category, while quercetin as a comparator has very strong antioxidant activity with IC50 value of 5.93 μg/mL.